FRI0001 Treating Experimental Arthritis with The Innate Immune Inhibitor IL-37 Reduces Joint and Systemic Inflammation. (15th July 2016) - Cavalli, G.; Koenders, M.; Kim, J.; Tan, A.C.; Garlanda, C.; Mantovani, A.; Dagna, L.; Joosten, L.; Dinarello, C.
Abstract : Background: Recently characterized as a fundamental inhibitor of innate and adaptive immune responses, IL-1 family member IL-37 curbs excessive inflammation and prevents tissue damage by suppressing the production of pro-inflammatory cytokines (1). Objectives: We investigated the effects of recombinant IL-37 on joint and systemic inflammation and joint pathology in a mouse model of arthritis. In addition, we explored the potential for therapeutic use in human joint inflammation. Methods: Wild-type (WT) mice were treated systemically with a recombinant form of the naturally occurring human IL-37, and then arthritis was induced via instillation of streptococcal cell wall (SCW) fragments in the knee joints; joint inflammation, histology, and synovial and systemic cytokine levels were evaluated after 24 hours. Mice deficient in IL-1 family decoy receptor IL-1R8 were similarly treated. The effects of IL-37 treatment were also assessed in a model of SCW-induced peritonitis. Changes in circulating and bone marrow neutrophils were evaluated. Gene expression of IL-37 and IL-1R8 was determined in the synovia of patients with rheumatoid arthritis (RA). Results: In WT mice, low doses (40 μg/kg) of IL-37 suppressed joint inflammation by 51.7% ( p <0.001). In the synovial extracts of IL-37-treated mice, IL-1β was reduced by 84% ( p <0.001), IL-6 by 73% ( p=0.002 ), TNFα by 33% ( p <0.001). These reductions were associated with a lower recruitment of neutrophils into the joint, as also demonstrated by a 60% reduction in synovial levels of the neutrophil enzyme MPO ( p <0.001). Consistently, IL-37 treatment was associated with a decrease in circulating and an increase in bone marrow neutrophils. Mechanistically, mice treated with IL-37 exhibited a marked decrease in synovial levels of main neutrophil chemo-attractants KC, CCL3/MIP1α, and IL-1α, and of circulating G-CSF. We show that the anti-inflammatory effects of IL-37 require the IL-1 family decoy receptor IL-1R8, as protective effects were abrogated in mice deficient for this receptor. These results were confirmed in a model of SCW-induced systemic inflammation, that is, peritonitis. We found that gene expression of IL-1R8, but not IL-37, is markedly increased in the synovia of patients with RA. Conclusions: The present study demonstrates that by curbing excessive inflammation IL-37 exerts a protective role against arthritis. Short-term, low-dose treatment with recombinant IL-37 suppressed joint inflammation, reduced cell influx, and lowered histologic scores by more than 50%. These effects were associated with suppression of synovial and systemic inflammatory cytokines and chemokines, leading to a reduced recruitment of neutrophils to the joint. We also demonstrate that IL-37 is scarcely expressed in the diseased synovia of patients with RA, but expression of IL-1R8, the receptor transducing the anti inflammatory effects of IL-37, is elevated. Thus, while levels of endogenous IL-37 are too low to contain the overwhelming inflammatory reaction in the synovia of RA patients, exogenous administration may suppress the pathological process. References: Nold MF, et al. IL-37 is a fundamental inhibitor of innate immunity. Nat Immunol. 2010 Disclosure of Interest: None declared